2007
DOI: 10.2967/jnumed.107.041673
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Biologic Evaluation of a Novel Radioiodinated Benzylpiperazine, 123I-MEL037, for Malignant Melanoma

Abstract: Radiopharmaceuticals that can target the random metastatic dissemination of melanoma tumors may present opportunities for imaging and staging the disease as well as potential radiotherapeutic applications. A novel molecule, 2-(2-(4-(4-123 Iiodobenzyl)piperazin-1-yl)-2-oxoethyl)isoindoline-1,3-dione (MEL037), was synthesized, labeled with 123 I, and evaluated for application in melanoma tumor scintigraphy and radiotherapy. Methods: The tumor imaging potential of 123 I-MEL037 was studied in vivo in C57BL/6J fema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 25 publications
(34 reference statements)
1
29
0
Order By: Relevance
“…This is likely due to the specific interaction of 18 F-MEL050 with melanin, because no 18 F-MEL050 is retained in these tissues in nonpigmented BALB/c nude mice or in A375 amelanotic tumor grafts. This result is in agreement with previously reported results for 123 I-MEL037, 125 I-BZA, and 125 I-BZA 2 , all exhibiting high affinity for melanin (22,30,31). Moreover, despite a high 125 I-BZA 2 uptake in the eyes of C57BL/6 mice, clinical trials with 123 I-BZA 2 have shown no significant accumulation in human eyes and even demonstrated the feasibility of imaging ocular melanoma with melanin-specific probes (19).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…This is likely due to the specific interaction of 18 F-MEL050 with melanin, because no 18 F-MEL050 is retained in these tissues in nonpigmented BALB/c nude mice or in A375 amelanotic tumor grafts. This result is in agreement with previously reported results for 123 I-MEL037, 125 I-BZA, and 125 I-BZA 2 , all exhibiting high affinity for melanin (22,30,31). Moreover, despite a high 125 I-BZA 2 uptake in the eyes of C57BL/6 mice, clinical trials with 123 I-BZA 2 have shown no significant accumulation in human eyes and even demonstrated the feasibility of imaging ocular melanoma with melanin-specific probes (19).…”
Section: Discussionsupporting
confidence: 94%
“…More recently, a preclinical imaging study by our group demonstrated that a novel iodobenzylpiperazine, 123 I-MEL037, had rapid and 3-fold higher tumor uptake than 123 I-BZA 2 , suggesting a potential for both melanoma imaging and therapeutic applications (22). A preliminary study also reported the synthesis and biodistribution of a PET radiopharmaceutical, N-(2-diethylaminoethyl)-4-18 Ffluorobenzamide (FBZA), showing great promise for PET (23).…”
mentioning
confidence: 99%
“…The cells were maintained in DMEM medium (Invitrogen, Carlsbad, CA) supplemented with 10% fetal bovine serum (FBS) (Invitrogen, Carlsbad, CA). B16F10 cells expressing sigma receptors [12] were used as model cells in our study.…”
Section: Methodsmentioning
confidence: 99%
“…The four heterocycles chosen are all structural modifications of the piperazine core, known for its stability, 27 to observe what effect this change to stability, flexibility/rigidity would have on the in vivo behavior of the molecules. The synthesis began with the corresponding Boc protected intermediates (26,31,36), which were N-alkylated with either 4-iodo or 4-bromobenzyl bromide to give 27−28, 32−33, and 37−38 followed by Boc-deprotection with TFA and isolation as the free amine as described in Scheme 2.…”
Section: ■ Results and Discussionmentioning
confidence: 99%